PERBEDAAN ASUPAN GIZI TERHADAP KADAR HEMOGLOBIN PADA REMAJA PUTRI YANG BERSEKOLAH DI FULL DAY SCHOOL DENGAN NON FULL DAY SCHOOL (Studi di SMA Negeri 1 Sragi & SMA Islam Wonopringgo Kabupaten Pekalongan) - Nurul Latifah; Laksmi Widajanti; M. Zen Rahfiluddin (Jurnal Kesehatan Masyarakat, 2019)
Full day school and non full day school policies with different rest allocations cause changes in eating patterns, namely lunch at school so that the body's nutritional needs are not met, the impact of the synthesis process is disturbed if it occurs continuously, it will cause anemia. The research objective is to determine differences in nutritional intake on hemoglobin levels in adolescent girls who attend full day school (FDS) with non full day school (NFDS). Nutrient intake includes energy, protein, iron and vitamin C. Comparative study method with cross sectional approach with stratified random sampling technique. The number of samples is 35 per school. Data analysis using Independent T-test, Mann Whitney, Pearson Correlation and Spearman Rank test. The results showed that the majority of the FDS Energy Adequacy Level was 77.1% less than the NFDS of 97.1% and the normal category FDS hemoglobin level was 68.6% smaller than the NFDS of 77.1%. Protein Adequacy Level , iron, vitamin C of 68.6%, 85.7%, 74.3% in the FDS category less, greater than NFDS namely 51.4%, 57.1%, 65.7%. Conclusions are There are differences in the level of iron adequacy in young women in FDS & NFDS (P value = 0.001) and there are no differences in levels of hemoglobin, levels of energy, protein, and vitamin C adequacy in young women in FDS & NFDS (p value = 0.408, 0.651, 0.902, 0.321). Suggestions from research are that full day school can provide food sources of protein and iron from animals that are appropriate, whereas for non full day schools can maintain good consumption patterns